Central Technical Archive of Construction in Tirana, between two totalitarian political systems - Armand Vokshi (Disegnare con)
The Central Technical Construction Archive (AQTN) represents a key institution for the preservation of technical documentary heritage in Albania, safeguarding valuable materials that span a wide historical period, from the early years of the communist regime to the present day. This archival structure contains construction projects, technical documentation, urban plans, building standards, and graphic materials that reflect the country’s urban, architectural, and engineering development over the decades. This paper presents a chronological and thematic analysis of the organization of AQTN, including its division according to historical periods and the main categories of preserved documentation. Special attention is given to the archive’s importance for scientific research, urban planning, and the protection of technical heritage, as well as to the challenges related to digitization and public access to its collections. Through specific examples of preserved projects, the paper highlights the transformation of construction and planning concepts in Albania, revealing the intertwining of ideological, technical, and economic influences in the development of the built environment. This work aims to raise awareness of AQTN’s significance as a unique resource for interdisciplinary studies in the fields of architecture, engineering, urban history, and cultural heritage. DOI: https://doi.org/10.20365/disegnarecon.34.2025.10